PERSEPSI GENERASI Z TERHADAP NILA-NILAI MODERASI BERAGAMA DARI DAKWAH MEDIA SOSIAL TIKTOK - Rosfiani, Okta; Aulia, Vina; Fadhillah, Muhammad Rizky; A'zizah, Hikmatussalmah Nur; Maulana, Rijal; Islami, Muhammad Ridwan Al; Zamany, Alfia Zahra (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT The social media platform TikTok has become a significant medium for Islamic  preaching (dakwah), particularly among Generation Z. This quantitative study aims to analyze Generation Z's perceptions of religious moderation values conveyed through dakwah content on TikTok. Religious moderation in this study is understood as an attitude emphasizing balance, tolerance, non-violence, and harmony in religious life. The research uses a descriptive quantitative approach with a survey method. Data was collected through an online questionnaire distributed to 100 Generation Z respondents (born 1997-2012) who actively use TikTok and have been exposed to dakwah content on the platform. The results show that, in general, Generation Z's perceptions of the religious moderation values conveyed through TikTok dakwah tend to be positive. Most respondents view that the dakwah content they encounter emphasizes values of compassion, interfaith tolerance, and the rejection of radicalism. However, the findings also reveal variations in perception. On one hand, dakwah content presented creatively and in an accessible manner is considered effective in conveying messages of moderation. On the other hand, some respondents expressed skepticism regarding the depth of the material and concerns about the potential for oversimplified delivery or even the existence of dakwah content with exclusive nuances. The implication of this research is the importance for digital religious communicators to pay more attention to source credibility, depth of substance, and communication strategies that are creative yet comprehensive in spreading religious moderation values, so that the messages conveyed are not only viral but also foster a complete and balanced understanding for Generation Z. ABSTRAK Media sosial TikTok telah menjadi platform dakwah yang signifikan, terutama di kalangan Generasi Z. Penelitian kuantitatif ini bertujuan untuk menganalisis persepsi Generasi Z terhadap nilai-nilai moderasi beragama yang disampaikan melalui konten dakwah di TikTok. Moderasi beragama dalam studi ini dipahami sebagai sikap yang menekankan keseimbangan, toleransi, anti-kekerasan, dan keselarasan dalam kehidupan beragama. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan metode survei. Data dikumpulkan melalui kuesioner online yang disebarkan kepada 100 responden Generasi Z (kelahiran 1997-2012) yang aktif menggunakan TikTok dan pernah terpapar konten dakwah di platform tersebut. Hasil penelitian menunjukkan bahwa secara umum, persepsi Generasi Z terhadap nilai moderasi beragama dari dakwah TikTok cenderung positif. Sebagian besar responden memandang bahwa konten dakwah yang mereka temui lebih banyak menekankan pada nilai-nilai kerahmatan, toleransi antarumat beragama, dan penolakan terhadap radikalisme. Namun, temuan juga mengungkap adanya variasi persepsi. Di satu sisi, konten dakwah yang disajikan secara kreatif dan ringan dinilai efektif dalam menyampaikan pesan moderasi. Di sisi lain, sebagian responden menyatakan skeptisisme terhadap kedalaman materi dan kekhawatiran terhadap potensi penyampaian yang terlalu simplistik atau bahkan adanya konten dakwah yang justru bernuansa eksklusif. Implikasi dari penelitian ini adalah pentingnya para pendakwah digital untuk lebih memperhatikan kredibilitas sumber, kedalaman substansi, dan strategi komunikasi yang kreatif namun tetap menyeluruh dalam menyebarkan nilai-nilai moderasi beragama.